The Effect of Application Middle Level Violin Textbooks on Violin Playing Skills in the Music Study Program, Faculty of Languages and Arts, Universitas Negeri Surabaya - Vivi Ervina Dewi (Gondang: Jurnal Seni dan Budaya, 2023)
This research aims to find out significant differences in violin playing skills between students who were taught using an intermediate level violin textbook made by a team of lecturers and students who were not taught using an intermediate level violin textbook made by a team of lecturers in the Music Study Program, Universitas Negeri Surabaya. The research method used is a quantitative method with a quasi-experimental type. Research result is known that the violin playing skills between the experimental group and the control group differ significantly. This conclusion is proven by the mean score of the experimental group which is higher than the control group in the posttest activity. The mean posttest score in the experimental group was 88.45. Meanwhile, the mean posttest score in the control group was 82.65. Another thing is also shown by the results of the independent sample t-test in the experimental group and the control group during the posttest activity with a calculated t value of 6.104 and a t table value of 2.086. The calculated t value > t table value, so it can be said that the experimental group and the control group differ significantly. Therefore, there is an influence of the application of an intermediate level violin textbook made by a team of lecturers on violin playing skills in the Music Study Program, Universitas Negeri Surabaya. The increase in violin playing skills was more demonstrated in the experimental group than the control group. This argument is proven by the mean pretest score in the experimental group of 81.15, while the mean pretest score in the control group is 80.7. The mean posttest score for the experimental group was 88.45, while the mean posttest score for the control group was 82.65. The experimental group experienced an increase of 7.3. This is shown from the mean score of 81.15 at the pretest which increased to 88.45 at the posttest. Meanwhile, the control group also experienced an increase in the mean score of 1.95.